2020
DOI: 10.1021/acs.jpcc.0c08492
|View full text |Cite
|
Sign up to set email alerts
|

Hot Carrier Mobility Dynamics Unravel Competing Subpicosecond Processes in Lead Halide Perovskites

Abstract: The outstanding photovoltaic performances of lead halide perovskite (LHP) thin film solar cells are due in particular to the large diffusion length of photocarriers. The mechanism behind this property and its dependence on the various anions and cations in the LHP material composition are still an active topic of debate. Here, we apply ultrabroadband terahertz spectroscopy with a time resolution ≤ 200 fs to probe the early carrier mobility dynamics of photoexcited perovskite samples of different chemical compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
20
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 46 publications
3
20
1
Order By: Relevance
“…A similar argument is valid to exclude charge-carrier cooling as the potential source of the early time reduction in photoconductivity: given that higher-lying bands in metal-halide perovskites have lower curvature (higher effective mass), charge-carrier relaxation into the more curved (lower effective mass) band extrema should lead to a rise in charge-carrier mobility and thus photoconductivity. This has been observed in excess-energy dependent OPTP spectroscopy in conventional metal-halide perovskites , but is the opposite to what is observed here for Cu 2 AgBiI 6 . Given this, we argue that the thermally activated hopping mobility μ loc indicates the formation of small polarons or self-trapped carriers in Cu 2 AgBiI 6 , as outlined above, at the lowest point of the bandstructure. ,, …”
contrasting
confidence: 94%
“…A similar argument is valid to exclude charge-carrier cooling as the potential source of the early time reduction in photoconductivity: given that higher-lying bands in metal-halide perovskites have lower curvature (higher effective mass), charge-carrier relaxation into the more curved (lower effective mass) band extrema should lead to a rise in charge-carrier mobility and thus photoconductivity. This has been observed in excess-energy dependent OPTP spectroscopy in conventional metal-halide perovskites , but is the opposite to what is observed here for Cu 2 AgBiI 6 . Given this, we argue that the thermally activated hopping mobility μ loc indicates the formation of small polarons or self-trapped carriers in Cu 2 AgBiI 6 , as outlined above, at the lowest point of the bandstructure. ,, …”
contrasting
confidence: 94%
“…54 More recent studies have focused on the sub-ps timescale with a view to explore the carrier cooling dynamics. [57][58][59][60] Generally, these reports echo the results of the aforementioned transient absorption studies in that they show a delayed build-up of the signal for higher energy excitations. Bretschnedier et al showed that this build-up cannot be solely attributed to carrier 6 cooling, and contains an intrinsic term for polaron formation (~400 fs in the case of MAPbI3).…”
Section: Main Textsupporting
confidence: 66%
“…The reduced mobility of the hot states may be due to an increase in their effective mass, as outlined in recent works. 60,68 However, taking the delayed response of the THz dynamics following the IR push, we suggest that this reduced mobility is instead caused by a temporary localized heating 69 of the MHP lattice, associated with the immediate vicinity of the localized charge-carrier (polaron). The small volume of this polaron leads to a high effective lattice temperature, and substantial reduction of the carrier mobility.…”
Section: Fig 2 Representative Pump-push-probe Transients (Left) Push-...mentioning
confidence: 84%
“…We attribute this to charge-carrier relaxation preceding localization, when photoexcitation occurs well above the band gap. Studies of conventional metal-halide perovskites using OPTP spectroscopy have found slower rises in photoconductivity with increasing pump energy, [89,90] attributed to charge-carrier relaxation occurring within the first hundreds of femtoseconds: as relaxation to the bottom of the band takes place, the charge-carrier mobility increases because the band extrema are more highly curved, leading to a rise in photoconductivity response over the relaxation timescale. Such a pronounced rise in mobility (and thus photoconductivity) over the first few hundred femtoseconds is not observed in the silver-bismuth materials studied here, most likely because of the very flat band structure found in such materials, [6,91] which would lead to little change in mobility as carriers relax.…”
Section: (10 Of 15)mentioning
confidence: 99%